Glyphosate and AMPA in Human Urine of HBM4EU-Aligned Studies: Part B Adults - Jurgen Buekers; Sylvie Remy; Jos Bessems; Eva Govarts; Loïc Rambaud; Margaux Riou; Thorhallur I Halldorsson; Kristin Ólafsdóttir; Nicole Probst-Hensch; Priska Ammann; Till Weber; Marike Kolossa-Gehring; et al. (Toxics, 2022)
Within HBM4EU, human biomonitoring (HBM) studies measuring glyphosate (Gly) and aminomethylphosphonic acid (AMPA) in urine samples from the general adult population were aligned and quality-controlled/assured. Data from four studies (ESB Germany (2015–2020); Swiss HBM4EU study (2020); DIET-HBM Iceland (2019–2020); ESTEBAN France (2014–2016)) were included representing Northern and Western Europe. Overall, median values were below the reported quantification limits (LOQs) (0.05–0.1 µg/L). The 95th percentiles (P95) ranged between 0.24 and 0.37 µg/L urine for Gly and between 0.21 and 0.38 µg/L for AMPA. Lower values were observed in adults compared to children. Indications exist for autonomous sources of AMPA in the environment. As for children, reversed dosimetry calculations based on HBM data in adults did not lead to exceedances of the ADI (proposed acceptable daily intake of EFSA for Gly 0.1 mg/kg bw/day based on histopathological findings in the salivary gland of rats) indicating no human health risks in the studied populations at the moment. However, the controversy on carcinogenicity, potential endocrine effects and the absence of a group ADI for Gly and AMPA induce uncertainty to the risk assessment. Exposure determinant analysis showed few significant associations. More data on specific subgroups, such as those occupationally exposed or living close to agricultural fields or with certain consumption patterns (vegetarian, vegan, organic food, high cereal consumer), are needed to evaluate major exposure sources.